Influence Of Giving Kangaroo Mother Care On Body Temperature and Oxygen Saturation On Low Birth Weight - Sri Ely Riani; Orachorn Lumprom (Open Access Health Scientific Journal, 2023)
Background: Treatment of Kangaroo Methods has begun to be recommended at this time for women with low birth weight (LBW) babies because the birth of low birth weight babies both premature and dismatur is one of the biggest causes of infant death. This study aimed to analyze the effect of the kangaroo treatment method on changes in body temperature and oxygen saturation in newborn babies.Methods: The research design is a pre-experimental one group pre-and post-test conducted in the perinatology room. The population of this research is the whole LBW in the Perinatology Room of the Soedomo Trenggalek Regional General Hospital. There are 15 newborn babies who meet the inclusion criteria selected as a sample by using Purposive Sampling technique. This research uses observation sheets as instruments. Results of statistical analysis using paired t test. Results: The results showed that there was a significant effect of kangaroo mother care on changes in body temperature and oxygen saturation in newborn babies ie pre temperature obtained mean 36.20C and post temperature obtained mean 370C this shows an increase of body temperature towards normal temperature (p value = 0.000) < value of α of 0.01. While the pre-saturation mean is 90% and the post-95% saturation mean, this indicates an increase in oxygen saturation towards normal (p value=0.000) < value of α of 0.01. Conclusion: The kangaroo treatment method is an effective, easy and inexpensive way to care for a baby with LBW while in hospital or for home treatment. Baby's and mother's skin contact directly on the treatment of kangaroo methods can maintain the stability of body temperature and oxygen saturation. The more often the mother performs kangaroo treatment on the baby then the satability of body temperature and oxygen saturation will be more awake and this will accelerate the process of improving the condition of LBW towards better which can also improve the relationship (bonding) between mother and baby.